Interaction of people, livestock and the environment: Challenges for research - Smith, Jimmy W. (Ethiopian Society of Animal Production, 2000)
One of the great challenges facing the world over the next decades is to preserve its natural resource base while at the same time producing sufficient food to satisfy the demands of a growing human population. This paper outlines the important functions livestock perform particularly to the worlds' poor in Africa, Latin America and Asia, in addition to the indispensable contribution of livestock to meeting food demands. This paper also looks into the different views, of different societies all over the world, on the importance of livestock. The paper also discusses what is needed for decision making regarding the role of livestock in sustainable agriculture.